Walker regime for walls in ferromagnetic nanotubes. (June 2018) - Carbou, Gilles
Abstract: Ferromagnetic nanotubes are proposed as an alternative to ferromagnetic nanowires for data-storage applications. In this paper, we consider a two-dimensional model for such devices and we establish the stability of moving walls in the Walker regime when the tube is subject to a small magnetic field.